Innate immunity in Alzheimer’s disease: the relevance of animal models? - Franco Bocanegra, Diana K. (J Neural Transm (Vienna), 2017)
The mouse is one of the organisms most widely used as an animal model in biomedical research, due to the particular ease with which it can be handled and reproduced in laboratory. As a member of the mammalian class, mice share with humans many features regarding metabolic pathways, cell morphology and anatomy. However, important biological differences between mice and humans exist and must be taken into consideration when interpreting research results, to properly translate evidence from experimental studies into information that can be useful for human disease prevention and/or treatment. With respect to Alzheimer’s disease (AD), much of the experimental information currently known about this disease has been gathered from studies using mainly mice as models. Therefore, it is notably important to fully characterise the differences between mice and humans regarding important aspects of the disease. It is now widely known that inflammation plays an important role in the development of AD, a role that is not only a response to the surrounding pathological environment, but rather seems to be strongly implicated in the aetiology of the disease as indicated by the genetic studies. This review highlights relevant differences in inflammation and in microglia, the innate immune cell of the brain, between mice and humans regarding genetics and morphology in normal ageing, and the relationship of microglia with AD-like pathology, the inflammatory profile, and cognition. We conclude that some noteworthy differences exist between mice and humans regarding microglial characteristics, in distribution, gene expression, and states of activation. This may have repercussions in the way that transgenic mice respond to, and influence, the AD-like pathology. However, despite these differences, human and mouse microglia also show similarities in morphology and behaviour, such that the mouse is a suitable model for studying the role of microglia, as long as these differences are taken into consideration when delineating new strategies to approach the study of neurodegenerative diseases.